Correlation Analysis of Helicobacter pylori Infection and Digestive Tract Symptoms in Children and Related Factors of Infection - Xiaohong YU; Dongjin FENG; Guangmeng WANG; Zhongmao DONG; Qi ZHOU; Yuan ZHANG (Tehran University of Medical Sciences, 2020)
Background: To analyze the correlation between Helicobacter pylori infection and digestive tract symptoms in children and other related factors, and to explore the risk factors of H. pylori infection in children and the expression of inflammatory factors in H. pylori-positive and H. pylori-negative children. Methods: Overall, 234 children with H. pylori test in Xuzhou Children's Hospital, Xuzhou Medical University (Xuzhou, China) were enrolled. Among them, 73 children were H. pylori-positive and 161 were H. pylori-negative. The expression levels of cytokines interleukin-8 (IL-8), interleukin-18 (IL-18) and interferon-γ (IFN-γ) in H. pylori-positive and H. pylori-negative children were determined by ELISA. The correlation between H. pylori-positive and general data, digestive tract symptoms, other clinical symptoms, living habits, eating habits, family history and other related factors was statistically analyzed. Multivariate Logistic regression analysis was used to analyze the independent risk factors of H. pylori infection in children. Results: Family monthly income, inattentive eating, sharing toothbrushes and cups, gnawing fingers, eating fried food, drinking raw water, eating smoked and pickled food, father suffering from gastropathy and mother suffering from gastropathy were independent risk factors for H. pylori infection in children. The most common digestive tract symptoms of children with H. pylori infection were abdominal pain, accompanied by one or more clinical symptoms. The expression levels of IL-8, IL-18 and IFN-γ in H. pylori-positive children were significantly higher than those in H. pylori-negative children. Conclusion: Prevention of H. pylori infection in children is helpful for healthy growth of children, and cytokines IL-8, IL-18, IFN-γ have the potential to be used as biomarkers for diagnosis of H. pylori-positive children.